PBL METHOD AND LEARNING MOTIVATION ARE INFLUENCED STUDENTS READING COMPREHENSION SKILL - Agus Tinah; Artanti Artanti; MGS Firdaus (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
his study aims to find out whether problem-based learning methods and learning motivation have an impact on the reading comprehension skills of eighth-grade students at SMPN 39 Palembang. 60 students from SMPN 39 Palembang were selected as samples for this study using a two-stage random selection procedure during the academic year 2022–2023. A factorial research design was used in this investigation. Tests and questionnaires were used to get the data.. When the data were studied using paired sample t-test, independent sample t-test, and two-way ANOVA test findings of 0.000 0.05, it was discovered that problem-based learning methods had a substantial impact on students' reading comprehension skills. Second, problem-based learning techniques have a considerable impact on students with low learning motivation who struggle with reading comprehension. Thirdly, students who use problem-based learning strategies and have high levels of learning motivation have a major impact on their ability to comprehend what they read. Finally, significant interactions between motivation and learning affect how well students understand recount texts taught by PBL and how well they understand SMPN 39 Palembang. Hence, both high and low-learner-motivation students benefited from the PBL approach.